SOCIAL MEDIA IN THE HOTEL AND RESTAURANT BUSINESS - Mendela, I.Ya.; Rumiantseva, I.B. (The actual problems of regional economy development, 2023)
Social media has become not only an integral part of our lives, but also an important channel of communication between businesses and customers. Customers use social media to find information about hotels and restaurants, learn about promotions and discounts, find reviews and ratings, and use it to connect with businesses. Social media also allows businesses to attract new customers, increase their reputation and interact with their audience. The scientific research was carried out on a topical topic in order to determine the role of social media in the hotel and restaurant business. After all, social media allows hotels and restaurants to connect with potential customers, provide information about their services, share photos and videos, and more. There are certain studies in the field of studying social media in the hotel and restaurant business, but research is needed in the direction of: defining the category apparatus, studying the properties of social media and revealing the main ways of using social media by hotels and restaurants. The purpose of the article is to analyze the advantages and disadvantages of using social media in the field of hotel and restaurant business. The systematic approach made it possible to highlight several examples of the use of social media in the hotel and restaurant business. The study points to the prospects of their application in the hotel and restaurant business. The scientific novelty of the study consists in determining the category apparatus of social media in the hotel and restaurant business. For the first time, the advantages and disadvantages of using social media in the field of hotel and restaurant business are highlighted. It also shows the prospects of using social media in the hotel and restaurant business. Previous studies were concerned with the analysis of social media in the context of the hotel or restaurant business, but this article points to the role of social media in the hotel and restaurant business as a whole. The practical significance of the research lies in the fact that the results of the work can be used in practice by enterprises of the hotel and restaurant business, which will increase the efficiency of their work. Scientific research in the field of using social media in the hotel and restaurant business is very important in order to increase the competitiveness of enterprises, improve interaction with customers, and identify trends in the industry. Overall, these studies should help to understand how to effectively use social media to improve business and attract more customers.